Profile of Primary Care professionals in the Municipality of Araranguá/SC (Research, Society and Development, 2020)
With advances in the scientific and technological fields, changes in health care models and health needs of the population, it is important to renew and broaden the knowledge of the multiprofessional team that works in Primary Care, since more and more professionals are required able to meet the health needs of the user and the service. This study aimed to investigate the sociodemographic, training and qualification characteristics of health professionals working in Primary Care in the city of Araranguá / SC. Methods: Descriptive, quantitative and transversal study, which was applied to health professionals, using a structured questionnaire for data collection. Results: 56 health professionals participated in the study, of which 46.6% were female, 57% were between 31 and 40 years of age, 62.5% had specialization, and 78.5 had some type of training in the last one five years. Conclusion: The results of this study demonstrate that health professionals working in Araranguá seek to carry out specializations and training, which is important for professional improvement and for changes in practice in services. Supported by the fact that professionals are already seeking qualification, it is suggested to encourage training as a qualification strategy for the Primary Care Network of the Municipality of Araranguá. The partnership with training institutions has a fundamental role, in the sense of reaffirming the importance of the teaching-service-community interaction, including the insertion of students from courses in the area in practice scenarios, as well as investments in multiprofessional residency programs.